Acute infection by Hiv-1: manifestaciones inusuales de laboratorio - Leoni, Alberto Francisco; Troyano, Zaida; Bilbao, Ines Maria D. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
The Acute Retroviral Syndrome shows nonspecific and variable clinical features. An incidence of 40-90% in those subjects exposed to HIV has been estimated. We report a case whose laboratories test presented uncommon changes such as an asymptomatic increasing of LDH, CPK with hepatic enzymes ten times up normal value. SGPT, hepatic enzyme was high by six months. Hemogram presented persistent leukopenia and limphomonocy- tosis. CPK, LDH and its isoenzimes should be checked to monitorize the follow up and syndrome progression or resolution, because of their increa sing when cellular lysis start, reaching a maximum value and then returning to normal value.